IMPROVING STUDENTS’ ACHIEVEMENT IN READING REPORT TEXT BY USING THINK-PAIR SHARE STRATEGY - Muhammad Faisal Situmorang and Bachtiar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study deals with improvement students’ achievement in reading report text by using Think Pair Share Strategy (TPS). This study was conducted by using classroom action research. The subject of the research was class X-2 SMA Negeri 1 Binjai with consists of 40 students. The research was conducted in two cycles and each cycle consists of three meetings and included orientation. The instruments for collecting data were quantitative data (multiple choice test) and qualitative data (diary notes, and observation sheet). Based on reading comprehension score, students score kept improving in every test. In orientation test the mean was 52,75, in cycle I the mean of reading test was 66,75, in cycle II the mean of reading comprehension score was 80,25. Based on diary notes, and observation sheet, it was found that teaching learning process ran well. Students were active and interested in reading report text. The result of the research showed that Think Pair Share Strategy (TPS) can improve students’ achievement in reading report text.